천연 색소 고정화 기술을 활용한 오미자와 자소엽 추출물 함유 음료의 항산화 활성 연구 - 신인순; 김성옥; 황수정; 김미려; 허담 (大韓本草學會誌, 2011)
Objectives: This study focused on Schisandrae Fructus (SF) and Perilae Folium (PF), traditional medicine herbs and health functional food in Korea, Japan and China. We investigated various pharmacological activities that include a potential source of free radical scavenging, anti-viral, anti-microbial, anti-allergy and anti-inflammatory activities. Methods: We conducted an investigation of total contents of phenolic and flavonoid compounds in these single herbal extraction with/without combined to mixture. We also measured antioxidant activities such as DPPH free radical scavenging, SOD-like scavenging, nitrite scavenging and hydroxyl radical scavenging activities, xanthine oxidase inhibition, linoleic acid peroxidation inhibition, and reducing power. Results: As the results, contents of total phenoilc compounds and flavonoids were higher in those of PF than those of SF. Those of SF+PF mixture showed the synergy effects compared with those of SF and PF single extractions. Activities of DPPH free radical and SOD-like scavenging in 1 mg/mL concentration increased in dose dependent manners. That of SF increased compared with that of PF. That of SF and PF mixture also increased compared with that of BHA as a positive control. The other antioxident activities also showed similar to patten of activity of DPPH free radical scavenging. When combined to SF and PF extractions, there was showed synergic effect compared with those of BHA, excepted activities of xanthine oxidase inhibition and reducing power. Taken together, SF and PF have high phenolic and flavonoid compounds content furthermore, antioxidant activities in SF and PF mixture showed more synergy effect compared with those of BHA. Conclusions: Therefore, these findings suggest that SF and PF mixture may offer functional materials potential for development of functional beverage. But further studies are needed for the identification of the active compounds.